Lift us up, don't push us out! : voices from the front lines of the educational justice movement - Warren, Mark R., 1955- (Boston, Massachusetts : Beacon Press, 2018)
"This book features the stories and voices of parents, young people, community organizers and educators describing how they are fighting systemic racism in schools by building a new educational justice movement committed to community-based, high quality, humane and empowering education for all young people"--
Introduction : building an educational justice movement / Mark R. Warren -- "I can't make a teacher love my son" : a black parent's journey to racial justice organizing / Zakiya Sankara-Jabar -- #SouthLAParentLove : redefining parent participation in South Los Angeles schools / Maisie Chin -- Speaking up and walking out : Boston students fight for educational justice / Carlos Rojas and Glorya Wornum -- Fighting for gender justice : girls of color assert their voice / Kate McDonough and Christina Powell -- The freedom to learn : dismantling the school-to-prison pipeline in the Southwest / Pam Martinez -- #FightForDyett : fighting back against school closings and the Journey 4 Justice / Jitu Brown -- There i no national without the local : grounding the school discipline movement in the Mississippi Delta / Joyce Parker -- The school Is the heart of the community : building community schools across New York City / Natasha Capers -- Fighting for teachers, children and their parents : building a social justice teachers union / Brandon Johnson -- Power, voting rights, and education in the South : organizing grassroots campaigns and building movements / Derrick Johnson -- Teachers unite! : organizing school communities for transformative justice / Sally Lee and Elana "E. M." Eisen-Markowitz -- Can schools nurture the souls of black and brown children? : combatting the school-to-prison pipeline in early childhood education / Roberta Udoh -- System change : following an inside-outside strategy as a school board member / Monica Garcia -- Walking into the community : community partnerships as a catalyst for institutional change in higher education / Maureen D. Gillette -- #schoolismyhustle : activist scholars and a youth movement to transform education / Vajra Watson -- Janitors are parents too! : promoting parent advocacy in the labor movement / Aida Cardenas and Janna Shadduck-Hernandez -- The same struggle : immigrant rights and educational justice / Jose Calderon -- Organizing intersectionally : trans and queer youth fighting for racial and gender justice / Geoffrey Winder -- Conclusion : educational justice as catalyst for a new social movement / Mark R. Warren.
Includes bibliographical references.
PB
Description based on print version record and CIP data provided by publisher.
Keywords: Community and school -- United States; Educational change -- United States -- Citizen participation; Educational equalization -- United States; Minorities -- Education -- Social aspects -- United States; EDUCATION / Educational Policy & Reform / General; EDUCATION / Organizations & Institutions; SOCIAL SCIENCE / Discrimination & Race Relations